STUDI PERKEMBANGAN PERUMAHAN DAN PENYEDIAAN FASILITAS DI CITRA RAYA - Fredrick Effendy; Liong Ju Tjung; Sylvie Wirawati (Jurusan Arsitektur dan Perencanaan, 2020)
Citra Raya is one of the new town in the Regency of Tangerang, Banten, which has been developed since 1994. This is the largest project of the Ciputra Group that stands on an area of 2,760 hectares. The development of Citra Raya is so rapid, the area of land that has been developed reaches 1,000 hectares. Currently Citra Raya has 51 residential clusters, including EcoHome which is the first apartment product. Citra Raya continues to present a variety of the latest facilities to meet the needs of its residents. The built facilities also continue to increase in scale as the services of Citra Raya develop. The purpose of this study is to determine the chronology / timeline of the development of housing and facilities in Citra Raya, determine the adequacy of the number of facilities built in Citra Raya to the standard needs of facilities, and knowing the relationship between housing development and the provision of facilities in Citra Raya. Data collection in this research was carried out by field surveys, interviews with developers, electronic media, and literature studies. Then there are five analyzes carried out, namely analysis of the development of Citra Raya, analysis of housing development, analysis of facility provision, analysis of facility adequacy, and analysis of the relationship between housing and facility development. Based on the results of the study note that the facilities in Citra Raya are sufficient for the residents in it. Even though some of the facilities are still lacking in terms of numbers, when viewed from the area of land that has been developed it meets existing standards. Then the development of housing and provision of facilities in Citra Raya has a strong positive relationship. The increase in the number of houses was also followed by the increase in the number of facilities. Keywords: development, facility, housing AbstrakCitra Raya merupakan salah satu kota baru yang berada di Kabupaten Tangerang, Banten, yang telah dikembangkan sejak tahun 1994. Proyek terbesar Ciputra Group ini berdiri di atas lahan seluas 2.760 hektar. Perkembangan Citra Raya begitu pesat, luas lahan yang telah dikembangkan mencapai 1.000 hektar. Saat ini Citra Raya memiliki 51 cluster perumahan, termasuk EcoHome yang merupakan produk apartemen pertama. Citra Raya terus menghadirkan beragam fasilitas terbaru untuk memenuhi kebutuhan penghuninya. Fasilitas yang dibangun juga terus bertambah skala pelayanannya seiring dengan berkembangnya Citra Raya. Penelitian ini bertujuan untuk mengetahui kronologi / timeline perkembangan perumahan dan fasilitas di Citra Raya, mengetahui ketercukupan jumlah fasilitas yang terbangun di Citra Raya terhadap standar kebutuhan fasilitas, dan mengetahui hubungan antara perkembangan perumahan dan penyediaan fasilitas di Citra Raya. Pengumpulan data dalam penelitian ini dilakukan dengan cara survei lapangan, wawancara dengan pengembang, media elektronik, serta studi pustaka. Lalu terdapat lima analisis yang dilakukan, yaitu analisis perkembangan Citra Raya, analisis perkembangan perumahan, analisis penyediaan fasilitas, analisis ketercukupan fasilitas, dan analisis hubungan perkembangan perumahan dan fasilitas. Berdasarkan hasil penelitian diketahui bahwa fasilitas yang ada di Citra Raya telah mencukupi kebutuhan penghuni di dalamnya. Meskipun beberapa fasilitas masih kurang dari segi jumlahnya, namun jika dilihat dari luas lahan yang terbangun telah memenuhi standar yang ada. Lalu perkembangan hunian dan penyediaan fasilitas di Citra Raya memiliki hubungan yang kuat positif. Bertambahnya jumlah hunian juga diikuti dengan bertambahnya jumlah fasilitas.